Photodynamic therapy applications – a review (Journal of Medical Science, 2023)
Photodynamic therapy (PDT) is a treatment method gaining worldwide attention. The paper overviews studies on PDT, as it may be applied in many medical disciplines, such as dermatology, urology, gynaecology, the therapy of head and neck cancers, and age-related macular degeneration. Recently, the development of this method has sped up, which is related to the appearance of new photosensitizers and optimised dosimetry of light. Current studies indicate that PDT is a significant support for conventional treatment protocols in many cases.